Assessment Contributing Factors related to hypothyroidism/hyperthyroidism for adult patient at Bagdad Teaching Hospitals - Sabah Abbas Ahmed; Ahmed Fleih Hassen (Kufa Journal for Nursing Sciences)
Objective (s):To assess of contributing factors related to hypothyroidism/ hyperthyroidism for adult patients, and to find out the relationship between some demographic characteristic (age, gender, level of education ) with contributing factors.